International port investment of Chinese port-related companies. (2nd August 2019) - Huo, Weiwei; Chen, Peggy Shu-Ling; Zhang, Wei; Li, Kevin X.
The devolution of Chinese port governance since the 1990s has resulted in not only private sectors' involvement in Chinese port investment and development but also allowing local port groups and terminal operators to implement international strategies to expand their business. This paper overviews the current implementation on international port investment of these two types of Chinese port-related companies. By analysing 39 international port investment cases, this paper finds the belt and road initiative (BRI) may promote China's investment in foreign ports. In addition, four main investment modalities are adopted, i.e., acquisition, joint venture, concession and build-operate-transfer (BOT). The companies mainly form a partnership for investment, and some of the investment projects involve an integration of the development of ports, industrial parks and cities. Of notice is that some investment projects are through a public-private partnership (PPP) model, i.e., Chinese companies as private entities and public sectors in the host countries.